Dry-method electrode composite binder, negative plate, preparation method of negative plate and lithium ion battery

The composite binder is prepared by co-precipitation of conductive agent dispersion and high molecular weight PTFE emulsion, which solves the problem of reaction between dry electrodes and lithium ions, improves the circulation performance and stability of the negative electrode sheet, and significantly improves the performance and service life of lithium ion batteries.

CN119552595APending Publication Date: 2025-03-04SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411735917.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

During the manufacturing process, the dry electrode has a problem of reacting with lithium ions to generate lithium fluoride, which leads to a decrease in battery capacity and uneven distribution of binder leads to attenuation of battery performance.

Method used

The composite binder is prepared by co-precipitation of conductive agent dispersion and high molecular weight PTFE emulsion. The negative electrode sheet is prepared by dry process, combining conductive agent and negative electrode active material to improve the adhesion stability.

Benefits of technology

It effectively weakens the reaction of binder with lithium ions, improves the circulation performance and stability of the negative electrode sheet, and significantly improves the performance and service life of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552595A_ABST
    Figure CN119552595A_ABST
Patent Text Reader

Abstract

The invention relates to a dry-method electrode composite binder, a negative plate, a preparation method of the negative plate and a lithium ion battery in the technical field of lithium battery production. The composite binder comprises conductive agent dispersion liquid and high-molecular-weight PTFE emulsion. The molecular weight of the macromolecular PTFE emulsion is not less than 500W. The mass ratio of the conductive agent dispersion liquid to the high-molecular-weight PTFE emulsion is (0.5-8): (92-99.5) after the conductive agent dispersion liquid and the high-molecular-weight PTFE emulsion are folded and fixed. The negative electrode plate is prepared by using the composite binder through a dry process. The invention also provides a preparation method. According to the invention, the conductive agent and the PTFE emulsion are precipitated into a new binder in a coprecipitation form, the composite material can realize passivation modification of the binder, weakening of reaction with lithium ions, enhancement of conductivity of active substances and improvement of cohesive stability, and meanwhile, the negative pole piece prepared by a dry method has relatively good cycle performance and stability and can be applied to the field of lithium ion batteries. The performance and the service life of the battery can be greatly improved, and the safety and the energy density of the battery are fundamentally improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery production, and in particular to a dry electrode composite binder, a negative electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art

[0002] The key performance of the lithium battery cell manufacturing process mainly depends on the manufacturing process of the electrode. At present, the manufacturing of electrode sheets is mainly divided into two types: wet and dry, but most of them use wet coating process. The disadvantage of this process method is that toxic and expensive organic solvents such as N, N-dimethylpyrrolidone (NMP) are usually used. During the manufacturing process, NMP will cause the battery to swell during the cycle and the performance will decay too quickly due to excessive water content. In addition, the evaporation and recovery of solvents during the manufacturing process will also cause huge energy consumption. Based on the above problems, the development of dry solvent-free manufacturing methods is cost-effective and environmentally friendly, which is of great significance in the lithium battery cell manufacturing process.

[0003] The dry process does not use solvents. It mainly mixes adhesives, active materials and conductive agents in a dry process, making it possible to manufacture thicker electrodes without worrying about uneven distribution of adhesives, thereby significantly improving energy density and reducing manufacturing costs. However, there are some urgent problems that need to be solved in dry electrodes. Due to the special production requirements of dry electrodes, the domestic dry process is currently based on fiberization manufacturing technology. The core material of this process is polytetrafluoroethylene (PTFE). However, if the binder is directly applied to the dry electrode, it will react with the lithium ions on the surface of the negative electrode to form lithium fluoride. The higher the PTFE content in the battery, the more lithium is consumed, reducing the capacity and weakening the bonding effect. In addition, the self-supporting film formed after PTFE fibrillation will still have the problem of reduced adhesion between the active material and the binder, and the shedding of the active material will increase the resistance inside the battery and affect the battery performance.

[0004] The present invention proposes a technical solution for solving the problem of dry electrode. Summary of the invention

[0005] In order to solve the above technical problems, the present invention discloses a dry electrode composite binder, a negative electrode sheet and a preparation method thereof, and a lithium ion battery. The technical solution of the present invention is implemented as follows:

[0006] The first aspect of the present invention provides a dry electrode composite binder material, comprising a conductive agent dispersion and a high molecular weight PTFE emulsion, wherein the molecular weight of the high molecular weight PTFE emulsion is not less than 500W.

[0007] The conductive agent dispersion of the present invention is a conductive agent mixed and dispersed in an aqueous solution, and the PTFE emulsion is an emulsion aqueous dispersion obtained by polymerizing tetrafluoroethylene monomer in water containing a surfactant.

[0008] In one embodiment, the conductive agent in the conductive agent dispersion includes one of superconductive carbon black (SP), graphene, carbon nanotubes (CNT), conductive graphite, carbon nanofibers, Ketjen black, carbon dots, and the like.

[0009] In one embodiment, the weight ratio of the conductive agent dispersion to the high molecular weight PTFE emulsion after solidification is (0.5-8): (92-99.5).

[0010] The second aspect of the present invention provides a negative electrode sheet, which includes the composite binder material provided in the first aspect of the present invention, a conductive agent and a negative electrode active material.

[0011] A third aspect of the present invention provides a method for preparing a negative electrode sheet by a dry process, comprising the following steps:

[0012] S1, mixing, stirring and dispersing the negative electrode main material and the conductive agent to obtain a first mixed material;

[0013] S2, adding a composite binder, mixing and stirring to obtain a second mixed material and drying the mixed material;

[0014] S3, dispersion for fibrillation;

[0015] S4, rolling the mold through a hot rolling mill and compounding it into a pole piece.

[0016] In the step S1, the mass ratio of the negative electrode main material to the conductive agent is (90-98): (0.5-5).

[0017] The negative electrode main material includes one of natural graphite, artificial graphite, soft carbon, hard carbon and activated carbon.

[0018] In the step S2, the mass ratio of the negative electrode main material to the composite binder is (90-98): (0.5-5).

[0019] The fourth aspect of the present invention provides a lithium-ion battery, which includes the negative electrode sheet provided by the second aspect of the present invention, which is prepared by the method provided by the third aspect of the present invention, and also includes a positive electrode sheet, a separator and an electrolyte.

[0020] The advantages of the present invention are as follows:

[0021] The composite binder is co-precipitated by a conductive agent dispersant and polytetrafluoroethylene (PTFE) emulsion. The conductive agent and PTFE emulsion are precipitated into a composite binder by co-precipitation. The composite material can realize the passivation modification of the binder, weaken the reaction with lithium ions, enhance the conductivity of the active material, and improve the stability of the adhesiveness. At the same time, the negative electrode sheet prepared by the dry method has good cycle performance and stability, which can greatly improve the performance and service life of the battery, and fundamentally improve the safety and energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only one embodiment of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] The same parts are denoted by the same reference numerals. It should be noted that the words "front", "rear", "left", "right", "upper" and "lower" used in the following description refer to directions in the drawings, and the words "bottom" and "top", "inner" and "outer" refer to directions toward or away from the geometric center of a specific component, respectively.

[0024] Figure 1 This is a picture of the composite adhesive in Example 1 of the present invention; as the only figure of the present invention, this figure is also designated as the abstract figure. DETAILED DESCRIPTION

[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0027] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0028] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0029] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.

[0030] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0031] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0032] Due to the special production requirements of dry electrodes, the domestic dry process is currently based on fiberization manufacturing technology. The core material of this process is polytetrafluoroethylene (PTFE). However, if the binder is directly applied to the dry electrode, it will react with the lithium ions on the surface of the negative electrode to form lithium fluoride. The higher the PTFE content in the battery, the more lithium is consumed, which reduces the capacity and weakens the bonding effect. In addition, the self-supporting film formed after the PTFE is fibrillated will still have the problem of reduced adhesion between the active substance and the binder, and the shedding of the active substance will lead to an increase in the internal resistance of the battery, thereby affecting the battery performance.

[0033] In order to solve the above problem, the present invention proposes a technical solution.

[0034] The first aspect of the present invention provides a dry electrode composite binder, comprising a conductive agent dispersion and a high molecular weight PTFE emulsion, wherein the molecular weight of the high molecular weight PTFE emulsion is not less than 500W.

[0035] The conductive agent dispersion of the present invention is a conductive agent mixed and dispersed in an aqueous solution, and the PTFE emulsion is an emulsion aqueous dispersion obtained by polymerizing tetrafluoroethylene monomer in water containing a surfactant.

[0036] In one embodiment, the conductive agent in the conductive agent dispersion includes one of superconductive carbon black (SP), graphene, carbon nanotubes (CNT), conductive graphite, carbon nanofibers, Ketjen black, carbon dots, and the like.

[0037] In one embodiment, the weight ratio of the conductive agent dispersion to the high molecular weight PTFE emulsion after solidification is (0.5-8): (92-99.5).

[0038] In one embodiment, the mass ratio of the conductive agent dispersion to the high molecular weight PTFE emulsion after solidification can be 1:90, 3:90, 5:90, 9:90, 10:90, 1:91, 1:95, 1:97, 1:99, 2:91, 2:95, 2:97: 2:99, 3:91, 3:95, 3:99, 5:95, 5:99, 7:95, 7:99, 9:95, 9:99, 10:95, 10:99, etc. The above values ​​are only examples, and the present invention does not impose any limitation thereto.

[0039] The composite binder prepared by the present invention is a composite binder co-precipitated by a conductive agent dispersant and a polytetrafluoroethylene (PTFE) emulsion. The material allows the conductive agent and the PTFE emulsion to be precipitated into a composite binder in the form of co-precipitation. The composite material can realize passivation modification of the binder, weaken the reaction with lithium ions, enhance the conductivity of the active material, and improve the stability of adhesion.

[0040] The second aspect of the present invention provides a negative electrode sheet, which includes the composite binder, a conductive agent and a negative electrode active material provided in the first aspect of the present invention.

[0041] In one embodiment, the conductive agent is selected from one or more of carbon black, conductive carbon, superconducting carbon, acetylene black, carbon nanotubes, Ketjen black, carbon dots, carbon fibers, graphene, and metal particles. Without exceeding the scope of understanding of those skilled in the art, those skilled in the art may freely implement the method, and the present invention does not impose any limitation on the method.

[0042] In one embodiment, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flaky, flake-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc. Without exceeding the scope of understanding of those skilled in the art, those skilled in the art can freely implement, and the present invention does not impose any restrictions on this.

[0043] A third aspect of the present invention provides a method for preparing a negative electrode sheet, which is a dry process and comprises the following steps:

[0044] S1, mixing, stirring and dispersing the negative electrode active material and the conductive agent to obtain a first mixed material;

[0045] S2, adding a composite binder, mixing and stirring to obtain a second mixed material and drying the mixed material;

[0046] S3, dispersion for fibrillation;

[0047] S4, rolling the mold through a hot rolling mill and compounding it into a pole piece.

[0048] In one embodiment, in the step S1, the mass ratio of the negative electrode active material to the conductive agent is (90-98): (0.5-5), the mixing and stirring temperature is 10°C-18°C, the revolution during stirring is 15r / min-25r / min, the rotation is 50r / min-100r / min, the stirring time is 10min-30min, and the dispersion time is 30min-60min.

[0049] In one embodiment, the mass ratio of the negative electrode active material to the conductive agent in step S1 can be selected from 90:0.5, 90:1, 90:2, 90:3, 90:4, 90:5, 92:1, 92:3, 92:5, 95:1, 95:5, 98:2, 98:3, etc., the stirring temperature can be selected from 10°C, 12°C, 14°C, 16°C, 18°C, etc.; the revolution speed can be selected from 15r / min, 18r / min, 20r / min, 23r / min, etc. / min, 25r / min, etc.; the rotation speed can be selected from 50r / min, 60r / min, 70r / min, 80r / min, 90r / min, 100r / min, etc.; the stirring time can be selected from 10min, 15min, 20min, 25min, 30min, etc., and the dispersion time can be selected from 30min, 35min, 40min, 45min, 50min, 55min, 60min, etc. The above numerical ratios are only examples and are not limited.

[0050] In one embodiment, in step S2, the mass ratio of the negative electrode active material to the composite binder is (90-98): (0.5-5), the mixing and stirring temperature is 10-18°C, the stirring time is 1h-2h, and the second mixed material is placed in an oven at a temperature of 90°C-140°C for 1h-2h.

[0051] In one embodiment, the mass ratio of the negative electrode active material to the composite binder in step S2 can be selected from 90:0.5, 90:1, 90:2, 90:3, 90:4, 90:5, 92:1, 92:3, 92:5, 95:1, 95:5, 98:2, 98:3, the stirring temperature can be selected from 10°C, 12°C, 14°C, 16°C, 18°C, etc.; the stirring time can be selected from 1h, 1.2h, 1.5h, 1.8h, 2h, etc., the oven temperature can be selected from 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, etc.; the holding time can be selected from 1h, 1.2h, 1.5h, 1.8h, 2h, etc. The above listed numerical ratios are only examples, and the present invention does not impose any limitation on this.

[0052] In one embodiment, in step S3, the second mixed material after being dispersed and dried is placed in a high-speed disperser, and the line speed is adjusted to 30m / s to 45m / s for 4min to 6min to perform fiberization.

[0053] Fibrillation refers to the process in which a material forms a fibrous structure with a certain direction and length under the action of external force.

[0054] In a high-speed disperser, the centrifugal force, shear force and impact force generated by the high-speed rotating dispersion disk fully mix the fibers and other components in the material, so that the polymer molecular chains in the material can be stretched and oriented to form a fibrous structure. The high-speed disperser can not only achieve fiberization, but also make the fibers in the material evenly distributed through its mixing and dispersing action, improve the uniformity and performance of the product, and achieve the ideal dispersion and fiberization effect.

[0055] In one embodiment, the dispersion time in step S3 can be selected to be 4 min, 5 min, 6 min, etc.; the line speed can be selected to be 30 m / s, 32 m / s, 35 m / s, 38 m / s, 40 m / s, 42 m / s, 45 m / s, etc.; the above values ​​are only examples, and the present invention does not impose any limitations on this.

[0056] The negative electrode sheet prepared by the dry method has good cycle performance and stability, which can greatly improve the performance and service life of the battery, and fundamentally improve the safety and energy density of the battery.

[0057] A fourth aspect of the present invention provides a lithium-ion battery, which includes the negative electrode sheet, the positive electrode sheet, the separator and the electrolyte provided in the second aspect of the present invention.

[0058] Positive electrode:

[0059] In one embodiment, the positive electrode sheet includes a current collector and a positive electrode active material layer disposed on the current collector.

[0060] In the present invention, the specific types of positive electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the positive electrode active material is selected from lithium nickel cobalt manganese oxide (Li(NiCoMn)O2), lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2) and lithium manganese oxide (LiMn2O4).

[0061] Diaphragm:

[0062] In one embodiment, the lithium battery and electrochemical device of the present invention are provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present invention are not particularly limited and can be any technology disclosed in the prior art.

[0063] In one embodiment, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0064] In one embodiment, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.

[0065] Electrolyte:

[0066] The lithium battery and electrochemical device of the present invention also include an electrolyte.

[0067] In one embodiment, the electrolyte includes a lithium salt and a solvent.

[0068] In one embodiment, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt.

[0069] In one embodiment, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB) or lithium di(difluorooxalatoborate) LiBF2(C2O4) (LiDFOB).

[0070] The embodiments of the present invention will be described in more detail below through examples and comparative examples. All examples and comparative examples are lithium ion battery sample groups prepared by the same process. It should be noted that the embodiments of the present invention are not limited to these examples.

[0071] Example 1

[0072] 1. Preparation of composite adhesive

[0073] 1) Add SP dispersion and high molecular weight PTFE emulsion into a 1L sandwich beaker at a 0.5:99.5 mass ratio after folding and solidification, and connect it to a high and low temperature constant temperature bath.

[0074] High molecular weight PTFE emulsion has a molecular weight of 600W.

[0075] 2) Keep the high and low temperature constant temperature bath at 15°C for 60 minutes, then maintain the linear speed at 1m / s, stir for 30 minutes, then raise the temperature to 80°C and continue stirring for 60 minutes.

[0076] 3) After standing for 60 minutes to cool, the mixture was passed through a 200-mesh sieve, and the material on the sieve was transferred to a vacuum drying oven and dried at 50° C. for 24 hours to obtain the composite adhesive.

[0077] SEM images of the composite adhesive are shown in Figure 1 As shown, the small ball-shaped aggregates in the middle are PTFE, and the honeycomb-shaped ones on the outside are SP. Due to the barrier effect of SP, PTFE can be dispersed into small aggregates of about 2 microns (conventional PTFE aggregates are 500 microns). Emulsion copolymerization makes the conductive agent and PTFE in a relatively uniform dispersion state in the initial form, and makes SP and PTFE adhere more closely.

[0078] 2. Preparation of negative electrode sheet

[0079] S1. Add the negative electrode main material graphite and conductive carbon in a mass ratio of 96:2 into a planetary stirring tank, use a double planetary stirrer (5L) to revolve at 20r / min and rotate at 50r / min at a temperature of 15°C, stir for 15min, and disperse for 30min to obtain a first mixed material;

[0080] S2, adding the composite binder prepared in step 1; the mass ratio of the negative electrode active material graphite to the composite binder is 96:2, maintaining the tank temperature at 15°C, stirring for 1.5 hours to obtain a second mixed material, and placing the second mixed material in an oven at 130°C for 1.5 hours;

[0081] S3, the heated second mixed material is placed in a high-speed disperser and dispersed for 5 minutes at a line speed of 40 m / s for fiberization;

[0082] S4, using a hot roller mill to roll and mold and composite into a negative electrode sheet.

[0083] 3. Preparation of positive electrode

[0084] The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed to prepare a positive electrode active material layer slurry, which is then coated on an aluminum foil and dried.

[0085] 4. Preparation of lithium-ion batteries:

[0086] The negative electrode sheet prepared in step 2 and the composite positive electrode prepared in step 3 are prepared into a lithium-ion battery together with a separator and an electrolyte using a traditional method.

[0087] After the preparation is completed, 20 lithium-ion battery samples are taken for the first efficiency test, and the test results are averaged.

[0088] The test method is as follows:

[0089] The test steps are set by the blue power test system (constant current charging 0.33C (voltage ≥ 4.3V), constant voltage charging (current ≤ 0.02C), standing for 10 minutes; constant current discharge 0.33C (voltage ≤ 2.8V),

[0090] The system reads the first effect.

[0091] Example 2

[0092] 1. Preparation of composite adhesive

[0093] 1) Add SP dispersion and high molecular weight PTFE emulsion into a 1L sandwich beaker at a weight ratio of 5:95 after solidification, and connect it to a high and low temperature constant temperature bath.

[0094] High molecular weight PTFE emulsion has a molecular weight of 600W.

[0095] 2) Keep the high and low temperature constant temperature bath at 15°C for 60 minutes, then maintain the linear speed at 1m / s, stir for 30 minutes, then raise the temperature to 80°C and continue stirring for 60 minutes.

[0096] 3) After standing for 60 minutes to cool, the mixture was passed through a 200-mesh sieve, and the material on the sieve was transferred to a vacuum drying oven and dried at 50° C. for 24 hours to obtain the composite adhesive.

[0097] 2. Preparation of negative electrode sheet

[0098] S1. Add the negative electrode main material graphite and conductive carbon in a mass ratio of 96:2 into a planetary stirring tank, use a double planetary stirrer (5L) to revolve at 20r / min and rotate at 50r / min at a temperature of 15°C, stir for 15min, and disperse for 30min to obtain a first mixed material;

[0099] S2, adding the composite binder prepared in step 1; the mass ratio of the negative electrode active material graphite to the composite binder is 96:2, maintaining the tank temperature at 15°C, stirring for 1.5 hours to obtain a second mixed material, and placing the second mixed material in an oven at 130°C for 1.5 hours;

[0100] S3, the heated second mixed material is placed in a high-speed disperser and dispersed for 5 minutes at a line speed of 40 m / s for fiberization;

[0101] S4, using a hot roller mill to roll and mold and composite into a negative electrode sheet.

[0102] 3. Preparation of positive electrode

[0103] The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed to prepare a positive electrode active material layer slurry, which is then coated on an aluminum foil and dried.

[0104] 4. Preparation of lithium-ion batteries:

[0105] The negative electrode sheet prepared in step 2 and the composite positive electrode prepared in step 3 are prepared into a lithium-ion battery together with a separator and an electrolyte using a traditional method.

[0106] After the preparation is completed, 20 negative electrode sheet samples are taken for wettability test, and the test results are averaged. The test method is the same as that of Example 1.

[0107] Example 3

[0108] 1. Preparation of composite adhesive

[0109] 1) Add SP dispersion and high molecular weight PTFE emulsion into a 1L sandwich beaker at a folded mass ratio of 8:92 and connect it to a high and low temperature constant temperature bath.

[0110] High molecular weight PTFE emulsion has a molecular weight of 600W.

[0111] 2) Keep the high and low temperature constant temperature bath at 15°C for 60 minutes, then maintain the linear speed at 1m / s, stir for 30 minutes, then raise the temperature to 80°C and continue stirring for 60 minutes.

[0112] 3) After standing for 60 minutes to cool, the mixture was passed through a 200-mesh sieve, and the material on the sieve was transferred to a vacuum drying oven and dried at 50° C. for 24 hours to obtain the composite adhesive.

[0113] 2. Preparation of negative electrode sheet

[0114] S1. Add the negative electrode main material graphite and conductive carbon in a mass ratio of 96:2 into a planetary stirring tank, use a double planetary stirrer (5L) to revolve at 20r / min and rotate at 50r / min at a temperature of 15°C, stir for 15min, and disperse for 30min to obtain a first mixed material;

[0115] S2, adding the composite binder prepared in step 1; the mass ratio of the negative electrode active material graphite to the composite binder is 96:2, maintaining the tank temperature at 15°C, stirring for 1.5 hours to obtain a second mixed material, and placing the second mixed material in an oven at 130°C for 1.5 hours;

[0116] S3, the heated second mixed material is placed in a high-speed disperser and dispersed for 5 minutes at a line speed of 40 m / s for fiberization;

[0117] S4, using a hot roller mill to roll and mold and composite into a negative electrode sheet.

[0118] 3. Preparation of positive electrode

[0119] The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed to prepare a positive electrode active material layer slurry, which is then coated on an aluminum foil and dried.

[0120] 4. Preparation of lithium-ion batteries:

[0121] The negative electrode sheet prepared in step 2 and the composite positive electrode prepared in step 3 are prepared into a lithium-ion battery together with a separator and an electrolyte using a traditional method.

[0122] After the preparation is completed, 20 negative electrode sheet samples are taken for wettability test, and the test results are averaged. The test method is the same as that of Example 1.

[0123] Comparative Example 1

[0124] 1. Choose PTFE as the binder

[0125] 2. Preparation of negative electrode sheet

[0126] S1. Add the negative electrode main material graphite and conductive carbon in a mass ratio of 96:2 into a planetary stirring tank, use a double planetary stirrer (5L) to revolve at 20r / min and rotate at 50r / min at a temperature of 15°C, stir for 15min, and disperse for 30min to obtain a first mixed material;

[0127] S2, adding the composite binder prepared in step 1; the mass ratio of the negative electrode active material graphite to the composite binder is 96:2, maintaining the tank temperature at 15°C, stirring for 1.5 hours to obtain a second mixed material, and placing the second mixed material in an oven at 130°C for 1.5 hours;

[0128] S3, the heated second mixed material is placed in a high-speed disperser and dispersed for 5 minutes at a line speed of 40 m / s for fiberization;

[0129] S4, using a hot roller mill to roll and mold and composite into a negative electrode sheet.

[0130] 3. Preparation of positive electrode

[0131] The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed to prepare a positive electrode active material layer slurry, which is then coated on an aluminum foil and dried.

[0132] 4. Preparation of lithium-ion batteries:

[0133] The negative electrode sheet prepared in step 2 and the composite positive electrode prepared in step 3 are prepared into a lithium-ion battery together with a separator and an electrolyte using a traditional method.

[0134] After the preparation is completed, 20 negative electrode sheet samples are taken for wettability test, and the test results are averaged. The test method is the same as that of Example 1.

[0135] Comparative Example 2

[0136] 1. Preparation of composite adhesive

[0137] 1) Add CNT dispersion and high molecular weight PTFE emulsion into a 1L sandwich beaker at a folded and solidified mass ratio of 0.5:99.5, and connect it to a high and low temperature constant temperature bath.

[0138] High molecular weight PTFE emulsion has a molecular weight of 600W.

[0139] 2) Keep the high and low temperature constant temperature bath at 15°C for 60 minutes, then maintain the linear speed at 1m / s, stir for 30 minutes, then raise the temperature to 80°C and continue stirring for 60 minutes.

[0140] 3) After standing for 60 minutes to cool, the mixture was passed through a 200-mesh sieve, and the material on the sieve was transferred to a vacuum drying oven and dried at 50° C. for 24 hours to obtain the composite adhesive.

[0141] 2. Preparation of negative electrode sheet

[0142] S1. Add the negative electrode main material graphite and conductive carbon in a mass ratio of 96:2 into a planetary stirring tank, use a double planetary stirrer (5L) to revolve at 20r / min and rotate at 50r / min at a temperature of 15°C, stir for 15min, and disperse for 30min to obtain a first mixed material;

[0143] S2, adding the composite binder prepared in step 1; the mass ratio of the negative electrode active material graphite to the composite binder is 96:2, maintaining the tank temperature at 15°C, stirring for 1.5 hours to obtain a second mixed material, and placing the second mixed material in an oven at 130°C for 1.5 hours;

[0144] S3, the heated second mixed material is placed in a high-speed disperser and dispersed for 5 minutes at a line speed of 40 m / s for fiberization;

[0145] S4, using a hot roller mill to roll and mold and composite into a negative electrode sheet.

[0146] 3. Preparation of positive electrode

[0147] The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed to prepare a positive electrode active material layer slurry, which is then coated on an aluminum foil and dried.

[0148] 4. Preparation of lithium-ion batteries:

[0149] The negative electrode sheet prepared in step 2 and the composite positive electrode prepared in step 3 are prepared into a lithium-ion battery together with a separator and an electrolyte using a traditional method.

[0150] After the preparation is completed, 20 negative electrode sheet samples are taken for wettability test, and the test results are averaged. The test method is the same as that of Example 1.

[0151] Comparative Example 3

[0152] 1. Preparation of composite adhesive

[0153] 1) Add graphene dispersion and high molecular weight PTFE emulsion into a 1L sandwich beaker at a folded mass ratio of 0.5:99.5, and connect it to a high and low temperature constant temperature bath.

[0154] High molecular weight PTFE emulsion has a molecular weight of 600W.

[0155] 2) Keep the high and low temperature constant temperature bath at 15°C for 60 minutes, then maintain the linear speed at 1m / s, stir for 30 minutes, then raise the temperature to 80°C and continue stirring for 60 minutes.

[0156] 3) After standing for 60 minutes to cool, the mixture was passed through a 200-mesh sieve, and the material on the sieve was transferred to a vacuum drying oven and dried at 50° C. for 24 hours to obtain the composite adhesive.

[0157] 2. Preparation of negative electrode sheet

[0158] S1. Add the negative electrode main material graphite and conductive carbon in a mass ratio of 96:2 into a planetary stirring tank, use a double planetary stirrer (5L) to revolve at 20r / min and rotate at 50r / min at a temperature of 15°C, stir for 15min, and disperse for 30min to obtain a first mixed material;

[0159] S2, adding the composite binder prepared in step 1; the mass ratio of the negative electrode active material graphite to the composite binder is 96:2, maintaining the tank temperature at 15°C, stirring for 1.5 hours to obtain a second mixed material, and placing the second mixed material in an oven at 130°C for 1.5 hours;

[0160] S3, the heated second mixed material is placed in a high-speed disperser and dispersed for 5 minutes at a line speed of 40 m / s for fiberization;

[0161] S4, using a hot roller mill to roll and mold and composite into a negative electrode sheet.

[0162] 3. Preparation of positive electrode

[0163] The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed to prepare a positive electrode active material layer slurry, which is then coated on an aluminum foil and dried.

[0164] 4. Preparation of lithium-ion batteries:

[0165] The negative electrode sheet prepared in step 2 and the composite positive electrode prepared in step 3 are prepared into a lithium-ion battery together with a separator and an electrolyte using a traditional method.

[0166] After the preparation is completed, 20 negative electrode sheet samples are taken for wettability test, and the test results are averaged. The test method is the same as that of Example 1.

[0167] Comparative experiment

[0168] Take six groups of samples in total, including Examples 1-3 and Comparative Examples 1-3, with 20 samples in each group. Perform the first-effect test on all the samples in each group, and take the average of the test results.

[0169] The test results are shown in the following table.

[0170] Sample set First effect / % Example 1 87.30 Example 2 87.24 Example 3 86.60 Comparative Example 1 86.35 Comparative Example 2 86.83 Comparative Example 3 87.12

[0171] According to the above table:

[0172] Compared with the comparative example 1 using pure PTFE as a binder, the superconductive carbon SP and PTFE emulsion are precipitated into a composite binder by coprecipitation in the example 1, and the first-effect performance is significantly improved. This shows that adding the conductive agent dispersion into the PTFE emulsion can effectively improve the performance of the negative electrode sheet, and thus improve the performance of the lithium-ion battery.

[0173] In Example 1, Example 2 and Example 3, the proportion of SP dispersion in the binder gradually increases, but the first-effect performance gradually decreases. However, it is still greater than the first-effect performance of Comparative Example 1.

[0174] The following conclusions can be drawn from Examples 1-3 and Comparative Examples: First, superconducting carbon SP and PTFE emulsion are precipitated into a composite binder by coprecipitation, and the negative electrode sheet prepared by the composite binder can effectively improve the initial performance of lithium-ion batteries. Second, within a certain range, the more the proportion of SP dispersion in the composite binder, the worse the effect, and the less the proportion, the better the effect.

[0175] According to Example 1, Comparative Example 2 and Comparative Example 3, it can be seen that using superconductive carbon SP and PTFE emulsion to precipitate a composite binder by coprecipitation is slightly better than using carbon nanotube CNT dispersion or graphene dispersion.

[0176] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A dry electrode composite binder, characterized in that: It includes conductive agent dispersion liquid and high molecular weight PTFE emulsion; the high molecular weight PTFE emulsion has a molecular weight of not less than 500W.

2. The dry electrode composite binder according to claim 1, characterized in that: The conductive agent dispersion is formed by mixing and dispersing the conductive agent in an aqueous solution; The PTFE emulsion is an emulsion aqueous dispersion obtained by polymerizing tetrafluoroethylene monomer in water containing a surfactant.

3. The dry electrode composite binder according to claim 1, characterized in that: The conductive agent in the conductive agent dispersion includes one of superconductive carbon black, graphene, carbon nanotubes, conductive graphite, carbon nanofibers, Ketjen black, carbon dots and the like.

4. The dry electrode composite binder according to claim 1, characterized in that: The mass ratio of the conductive agent dispersion to the high molecular weight PTFE emulsion after solidification is (0.5-8):(92-99.5).

5. A negative electrode sheet comprising the dry electrode composite binder according to claims 1 to 4, a conductive agent and a negative electrode active material.

6. A method for preparing the negative electrode sheet as claimed in claim 5, characterized in that: The steps include: S1, mixing, stirring and dispersing the negative electrode main material and the conductive agent to obtain a first mixed material; S2, adding the dry electrode composite binder, mixing and stirring to obtain a second mixed material and drying; S3, dispersion for fibrillation; S4, rolling the mold through a hot rolling mill and compounding it into a pole piece.

7. The method according to claim 6, characterized in that In the step S1, the mass ratio of the negative electrode main material to the conductive agent is (90-98): (0.5-5).

8. The method according to claim 6, characterized in that In the step S1, the negative electrode main material includes one of natural graphite, artificial graphite, soft carbon, hard carbon and activated carbon.

9. The method according to claim 6, characterized in that In the step S2, the mass ratio of the negative electrode main material to the composite binder is (90-98): (0.5-5).

10. A lithium-ion battery comprising a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte; the negative electrode sheet is prepared by the method described in any one of claims 6 to 9.

Citation Information

Cited By

  • Conductive carbon coated modified PTFE / disulfide bond composite binder, positive plate and preparation method

    CN120737762A